Different seeding rates influence on weed population and growth performance of aerobic rice / Zainudin Mohd Nasir - Mohd Nasir, Zainudin (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa L.) is the most importance food resources in Asia and always been demanded as staple food for human being. Traditionally, rice was cultivated in irrigated system which requires huge water consumption. Due to climatic changes and unpredictable weather that lead to water scarcity, research institution Malaysia Agricultures Research Development Institute (MARDI) had introduced new planting techniques called aerobic rice in Malaysia. However, weed infestation in aerobic rice was found as major limitation for optimum yield production due to no standing water during cultivation period. Study was performed with the aims to identify weed population and growth performance of MRIA1 in different seeding rates. Experiment was conducted in greenhouse under RCBD with 3 replications. 3 seeding consist of 4, 6, and 8 seeds per trough were involved. Results shows most dominant weed species was Leptochloa chinensis followed by Fimbristylis miliacea, Ludwigia hyssopifolia, Ludwigia octovalvis, Monochoria vaginalis, Cyperus diformis and Ageratum conyzoides. Generally, MRIA 1 was performed in optimum condition were the highest plant was 127.8 cm and the lowest was about 108.83 at the non-weedy treatment during 60 days after transplanting and the higher result number of tillers was about 10 tiller and the lowest was 5 tillers. The result of chlorophyll content the higher was 45.07 and the lowest was 37.36. For the weed density the most dominant weed density is Leptochloa chinensis and at the weed dry weight result also the higher is Leptochloa chinensis compare to another weed. Thus, the best result under 6 seeding rates because give the lower weed population compare and give the best result for the plant growth analysis compare with seeding rate 4 and 8.